High resolution (e, 2e + ion) study of low-energy electron-impact ionization and fragmentation of tetrahydrofuran. (August 2015) - Ren, XueGuang; Pflüger, Thomas; Weyland, Marvin; Baek, Woon Yong; Rabus, Hans; Ullrich, Joachim; Dorn, Alexander
Synopsis: We study the low-energy ( E 0 = 26 eV) electron-impact induced ionization and fragmentation of tetrahydrofuran using an (e, 2e + ion) method. The momentum vectors and, consequently, the kinetic energies for all three final-state charged particles are determined. The ionic fragments are clearly identified in the experiment with a mass resolution of one atomic mass unit. The fragmentation pathways of tetrahydrofuran are investigated by measuring the ion kinetic energy spectra and the binding energy spectra where a binding energy resolution of 1.5 eV has been achieved.